Techno-economic feasibility assessment of grid-defection. (July 2019) - Liu, Hangyue; Azuatalam, Donald; Chapman, Archie C.; Verbič, Gregor
Highlights: MILP-based grid-defection feasibility assessment framework using user load priority. Optimal off-grid PV-battery size range: For pv /kW, optimal b /kWh is within pv < b <3 pv . Grid defection is feasible for customers who compromise reliability for lower cost. Abstract: The interest in off-grid solar PV system has grown significantly in recent years. The price of suitable batteries started to decline following the price trajectory of solar PV, the curtailment of solar feed-in-tariff in many countries and the increasing electricity price. These are some important factors for grid defection trends. In this paper, we analyse the reliability and levelised cost of electricity (LCOE) of residential off-grid customers' PV-battery systems in order to carry out a techno-economic feasibility study of grid-defection. In more detail, this study demonstrates how off-grid customers can trade-off reliability for LCOE of their PV-battery systems, taking into consideration the priority/user-preference of different load types in a household. Consequently, we propose a novel decision making tool to improve the performance of a dynamic home energy management system (HEMS). The HEMS is set up as a mixed-integer linear optimization (MILP) problem which is solved using a rolling-horizon approach for weekly and yearly simulations. Weekly simulations were first performed in order to investigate the optimal range of PV and battery size combinations based on reliability and LCOE, using a week with the lowest solar PV output and the highest demand. Given the optimal PV-battery size combinations, yearly simulations were performed to assess the reliability and LCOE of PV-battery systems of randomly selected residential households in the Ausgrid Solar Home Electricity Data . Simulation results over the critical time period of the year indicate that an off-grid PV-battery system is relatively feasible for customers who are willing to compromize lower reliability in exchange for a lower cost. The result however indicates that the cost is still higher compared with a grid-connected system.